The System Monitoring Laboratorium Electrical Engineering With Internet of Things Based To Be Smaart Campus - Sholihuddin Ayyubi; Izza anshory; Indah Sulistyowati; Dwi Hadidja (Universitas Muhammadiyah Sidoarjo, 2021)
Security is needed in all places, especially in an institution where there are expensive and important equipment, therefore we need a security device system to facilitate handling as early as possible. In this case we can take advantage of technology that contains the concept of smart laboratory which is applied to the laboratory room of the electrical engineering faculty of Muhammadiyah University of Sidoarjo. By utilizing NodemCU as a microcontroller combined with a mini Arduino, RFID is a laboratory user identification that is used as a trigger for the locked or opening of the Doorlock solenoid, monitoring the opening and closing of the doorlock solenoid can be monitored or via a smartphone via a notification sent by nodemCU via the Blynk application platform, that the device create an internet of things system and monitor laboratory conditions in real time